(untitled) (Journal of the College of Basic Education, 2023)
In this paper, the cheap circuit of key electromechanical are designed and implemented to provide protection to the buildings, so that, the code is given for authorized people to enter these places and are controlled from the inside and out remotely using a remote control that contains the special code with a very large probabilities up to (20,000,000 ) possibility. This design consists of two main parts, electronic and mechanic parts, is designed and implemented using the (Orcade program Version 16) with good results. The Designed electronic circuit (motor circuit) is operates at a specific time, the motor dominated by jagged spiral driven by two-way. The first circuit is controlled on the motor circuit clockwise while the second circuit is controlled on the motor for anti clockwise direction with the duration of time is determined by the designer. Program in (C++ language) is written to calculate the values of τ, w.